The Balance Sheet Effects of Exchange Rate Fluctuations in Emerging Markets - Asad, Bhushra Zamir (University of the Witwatersrand, Johannesburg, 2024)
The main objective of the research is to check the effect of GDP growth, beside baseline model for investment (including only previous investment, output growth and real interest rate), while in Tobin Q equation investment model including (change in real interest rate, equity value, exchange rate depreciation and lag term of investment growth on growth of real investment has been investigated) as Q ratio has been consider valid porky for Investment opportunities. The results have been obtained in scenario of eight Emerging Markets Chile, Czech Republic, Hungary, India, Mexico, Poland, South Africa and South Korean in order to check which estimation is more robust, and which model best forecast actual growth with respect to investment in selected emerging markets. Dynamic models have been used and in all countries except Chile, the significant influence of real GDP growth on real investment growth has been found in both models. Moreover, in scenario of South Korea, the influence of Real interest Rate has also been found. The practical implication and future direction of the study has also been discussed in detail
A research report submitted in fulfillment of the requirements for the Master of Management in Finance and Investments, In the Faculty of Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: EXCHANGE RATE; EMERGING MARKETS; DOLLARIZATION; SDG-8: Decent work and economic growth